Pattern of Clinical Medication Seeking for Import Malaria by Migrant Workers - Mahmudi, Muhammad; Yudhastuti, Ririh (Faculty of Public Health, 2015)
ABSTRACTNumber of malaria cases in Kabupaten Trenggalek in 2014 is 89 cases, and 83 cases are import malaria from migrant workers. Import malaria is transmitted across two areas and affects the clinical medication seeking. This research wants to describe the pattern of clinical medication seeking for import malaria by migrant workers in Puskesmas Pandean working area. This was cross sectional study with descriptive quantitative approach. Researchâs sample is 26 import malaria sufferers in 2013â2015 who has chosen purposively with inclusion criteria. Interview had used to get information about characteristics, place felt the symptom, first clinical medication seeking (place and time), clinical diagnosis, medication follow up, and recovery status. The result of the research shows 100% respondent is man and the age about 20-30 years old (53,8) who is working as agricultural laborers outside Java. Mostly of respondent feel the malaria symptoms in their working place (53,8%). The day seeks clinical medication at day three after symptom (34, 6%). Respondents that feel the symptom in Puskesmas Pandean working area chose Puskesmas as clinical medication place (42,3%), and hospital (19,2%) for them whose experience the malaria symptom in their working area. Puskesmas is chosen as clinical diagnosis place (69%) and only 11,5% respondent got medication follow up. Puskesmas is chosen as intermediate clinical medication place (60%) for 19,2% respondent that is not recovered well, although 20% go to Dukun. All of respondent chose the clinical medication as their prime medication. Need to make medication follow up visitation well complete.Keyword: pattern, clinical medication, import malaria, migrant worker